DIGITALIZATION AS THE BASIS FOR THE TRANSFORMATION OF THE TRANSPORT AND LOGISTICS INDUSTRY AND CUSTOMS REGULATION OF NEW UZBEKISTAN - E.V. Ladygina; U.Yuldashev (Scholar Express Journals, 2024)
Digitalization of the transport and logistics industry and its technologization are an integral element of further integration of the Republic of Uzbekistan into the world community. The analysis of digitalization processes in customs administration is carried out. The main directions of implementation and development of digitalization in the transport industry and customs regulation in the customs territory of the Republic of Uzbekistan and priority areas for the development of customs, business and logistics industry are identified
Keywords: Digitalization; world community; identified